Shale oil production processes - Speight, James G. (Gulf Professional Publishing, 2012)
Shale Oil represents a huge additional global fossil fuel resource. However, extracting oil from the shale is no simple task; much still needs to be understood to make the process more cost-effective to increase economic flow rates. Clear and rigorous, Oil Shale Production Process will prove useful for those scientists and engineers already engaged in fossil fuel science and technology as well as scientists, non-scientists, engineers, and non-engineers who wish to gain a general overview or update of the science and technology of fossil fuels. Not only does the book discuss the production processes but also provides methods which should reduce environmental footprint by properly addressing: surface mining and extraction processes, in situ conversion process and hydrotreatment. Covers production processes technologies such as: surface mining and retorting, in Situ Retoring and processes, direct and indirect retorting and hydrotreatment for shale oil. Methods which should reduce environmental footprint Easy-to-read understand overview of the chemistry, engineering, and technology of shale oil.
Keywords: Oil-shale industry.; Shale oils.; elektronické knihy; electronic books